2018
DOI: 10.1177/0017896918768638
|View full text |Cite
|
Sign up to set email alerts
|

Including the voices of children and young people in health policy development: An Irish perspective

Abstract: Objective: This paper presents findings of a qualitative study which explored children and young people’s understanding of health and the factors that contribute, or act as barriers, to healthy lifestyles. Views were elicited from consultations with children and young people as part of the process for the development of a National Obesity Policy in Ireland. Design: Child participatory methodology was used which prioritised the voice of the child in policy making. Methods: Two consultations were held – one with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Whilst parents and teachers could be involved in such interventions their input and whether they are considered positive role models by young people cannot be guaranteed [11]; innovative strategies to effectively work with teenagers are therefore called for. Other studies show the multiple challenges involved in achieving this but also point the way for approaches to be co-designed by and with young people and the avoidance of “top down” assumptions about what pupils “should” engage with [38,39]. For example, many young people have a limited experience of trying some (even commonly available) “healthier” foods such as fruits or vegetables therefore adults have a responsibility to find ways to tempt them to try and experiment with new flavours to encourage a healthier way of eating.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst parents and teachers could be involved in such interventions their input and whether they are considered positive role models by young people cannot be guaranteed [11]; innovative strategies to effectively work with teenagers are therefore called for. Other studies show the multiple challenges involved in achieving this but also point the way for approaches to be co-designed by and with young people and the avoidance of “top down” assumptions about what pupils “should” engage with [38,39]. For example, many young people have a limited experience of trying some (even commonly available) “healthier” foods such as fruits or vegetables therefore adults have a responsibility to find ways to tempt them to try and experiment with new flavours to encourage a healthier way of eating.…”
Section: Discussionmentioning
confidence: 99%
“…as research participant, advisor, co-researcher). Contemporary examples of young people's research participation can be found across a range of disciplines and areas, including (but not limited to) education (see Can & Göksenin 2017;Forde et al 2018), health (see From 2019;Martin et al 2018), family life (see Shah et al 2021), and social media and peer relationships (see Goodyear, Armour & Wood 2018;Hunter, van Blerk & Shand 2021). The increasing commitment to the 'meaningful' engagement of young people in research has been largely triggered in response to the United Nations Convention on the Rights of the Child (UNCRC) (UN 1989).…”
Section: Young People's Involvement In Researchmentioning
confidence: 99%
“…Such approaches are further defended by recourse to their emancipatory and inclusive potential of an otherwise disenfranchised and "vulnerable" group. In relation to health, research with children has taken a focus on their thoughts on health and illness (Brady et al, 2015), health care policy and service provision (Persson et al, 2017), healthy lifestyles and practices (Martin et al, 2018) and health promotion (From, 2017;Mengwasser & Walton, 2013).…”
Section: Children's Voices In Qualitative Researchmentioning
confidence: 99%